Performance evaluation of Energy-aware routing algorithm for wireless sensor networks. (International Journal of Engineering and Computer Science, 2017)
Wireless Sensor Networks (WSNs) have many sensor nodes having restricted battery power which transmit sensed data to the Base Station that requires high energy consumption. Numerous routing protocols have already been proposed in this regard getting energy efficiency in heterogeneous situations. Though, each protocol is inappropriate for heterogeneous WSNs. Efficiency of WSNs declines as varying the heterogeneity of sensor nodes. This paper has evaluated the performance of Energy efficient routing protocol (ERA) under numerous scenarios. MATLAB tool is employed for experimental purpose. The comparison indicates that the ERA has quite effective results over other protocols.